Application of available attributes and physical characteristics for learning through play in Malaysian preschools - Lim, Pei Li Pearly (Scholink, 2015)
The National Preschool Curriculum (NPC) of Malaysia introduced "Learning through Play" (LTP) as one of the major teaching and learning approaches for preschools. However, for holistic growth, learning environment for young children should also emphasize on quality built environment that are planned in alignment with the vision and principles of LTP and consideration of children's development psychology. The theory of affordances was utilized whereby the existence of affordance within the physical environment creates potential to be actualized and it is independent of the users, namely children. This paper examined application of available attributes and physical characteristics for LTP in private preschools within converted residential houses. For this purpose, four case study preschools in Johor Bahru were selected through purposive sampling for participant observation to observe available attributes and physical characteristics as well as gain an understanding on potential and actualized affordances for LTP in the respective preschools. After qualitative analysis, findings indicated that opportunities for learning through play within preschools were hindered by four main factors which included lack of materials, equipment and free will; allowable play and independent mobility factors; time factor and safety factor.